2020
DOI: 10.1155/2020/8815432
|View full text |Cite
|
Sign up to set email alerts
|

Learning Curve and Clinical Outcome of Biportal Endoscopic-Assisted Lumbar Interbody Fusion

Abstract: Interbody fusion is a common surgical technique for diseases of the lumbar spine. Biportal endoscopic-assisted lumbar interbody fusion (BE-LIF) is a novel minimally invasive technique that has a long learning curve, which can be a barrier for surgeons. Therefore, we analyzed the learning curve in terms of operative time and evaluated the outcomes of BE-LIF. A retrospective study of fifty-seven consecutive patients who underwent BE-LIF for degenerative lumbar disease by a single surgeon from January 2017 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
4
23
1
Order By: Relevance
“…An unneglected limitation of this study is the limited number of cases enrolled. Compared with the outcome reported by Kim et al, in which the technique of bi-portal endoscopy-assisted lumbar interbody fusion required approximately 34 cases to reach an adequate performance level ( 43 ), the limited number of cases may increase the statistical error and decrease the accuracy of the evaluation of the learning curve in our study. Considering the difficulty for beginners to adapt to both endoscopic lumbar operation and percutaneous pedicle screw implantation simultaneously, more cases and surgeons should be enrolled into studies for a better evaluation.…”
Section: Discussioncontrasting
confidence: 69%
“…An unneglected limitation of this study is the limited number of cases enrolled. Compared with the outcome reported by Kim et al, in which the technique of bi-portal endoscopy-assisted lumbar interbody fusion required approximately 34 cases to reach an adequate performance level ( 43 ), the limited number of cases may increase the statistical error and decrease the accuracy of the evaluation of the learning curve in our study. Considering the difficulty for beginners to adapt to both endoscopic lumbar operation and percutaneous pedicle screw implantation simultaneously, more cases and surgeons should be enrolled into studies for a better evaluation.…”
Section: Discussioncontrasting
confidence: 69%
“…Study of Choi et al 20 indicated that the operation time of UBE surgery was close to the average and remained stable after the 36 th cases. Kim et al 21 considered that at least 34 cases were required to achieve sufficient mastery of lumbar interbody fusion by UBE. A surgeon with no experience with endoscopic surgery was considered to achieve adequate UBE surgical ability in the 58 th cases according to the study of Park et al 22 .Comparation of the learning curve of UBE and other endoscopic surgery has reference significance for surgeons who have engaged in other spinal endoscopic techniques in the past.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…However, in the results of CUSUM analysis in this study, there was no significant difference in surgical failure rates among different phases of UBE surgery. Moreover, in previous studies using operation time as an evaluation index [20][21][22] , there was no difference in the complication rate among different learning phases.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Indeed, multiple studies have used operative time as a proxy for surgeon comfort. For example, in the context of biportal TLIF, it took 34 cases over approximately 400 days for operative times to plateau [ 43 ]. It should be noted, however, that extended learning curves are a theme across MIS spinal procedures and are almost certainly not unique to ELIFs [ 44 46 ].…”
Section: Endoscopic Techniques In the Broader Context Of Lumbar Inter...mentioning
confidence: 99%